Changes in Rape Myth Acceptance Among Undergraduates: 2010 to 2017 - Beshers, Sarah (Journal of interpersonal violence, 2021)
The objective of this study is to characterize changes in rape myth acceptance (RMA) among college students from 2010 to 2017. Two samples of undergraduates in a northeastern university in the United States participated in the study, consisting of 464 students in the fall semester of 2010 and 534 students in the spring semester of 2017. Participants took an anonymous web-based survey to measure levels of RMA. The instrument was a revised and updated version of the Illinois Rape Myth Acceptance scale. Data analysis was both descriptive and inferential. For all subscales and the overall total RMA, differences in scores by year of survey (2017 compared with 2010) were significant; 2017 scores were significantly lower than 2010 scores. The greatest differences were for the She asked for it and She lied subscales, 1.76 versus 2.62 (p < .001) and 2.26 versus 2.69 (p < .001), respectively. In both years, male students and younger students were significantly more likely to endorse rape myths. RMA among undergraduates at one northeastern university has lessened since 2010.